Comparison Between Transurethral Electrical Vaporization of Prostate (TUVP) And Transurethral Resection of Prostate (TURP) For The Treatment of Benign Prostatic Hyperplasia - رسلان خضر; ناصر حسان; أحمد علي (Latakia University Journal -Medical Sciences Series, 2021)
Objective: Comparing between transurethral electrical vaporization of prostate (TUVP) and transurethral resection of prostate (TURP) for treatment of benign prostatic hyperplasia with volume of less than (80 ml) in terms of efficacy and safety. Methods and Materials: A prospective comparative study was conducted for patients group attending the Urology Department at Tishreen University Hospital in Lattakia, who have been decided to perform endoscopic intervention (TURP or TUVP) for the treatment of BPH during the period between (1-5-2019) and (1-11-2020). Results: The patient sample was 58 patients, their ages ranged between (51-85) years, (39) patients (67.3%) underwent (TURP), and (19) patients (32.7%) underwent (TUVP). There was an improvement in IPSS after surgery that has become in the (TURP) group (5.49 ± 3.4) and in the (TUVP) group (6.56 ± 2.58) (P=1.070), there was no statistically significant difference. Perioperative bleeding was evaluated as moderate severity bleeding that occurred in (32) patients (82%) in the (TURP) group, and in two patients (10.5%) in the (TUVP) group (P<0.0001). While the severe bleeding that required blood transfusion occurred in (7) patients (18%) in the (TURP) group, and it did not occur in any patient in the (TUVP) group, (P = 0.05), there was a statistically significant difference. The Study showed that there was no statistically significant difference between the two groups in terms of the following complications: transurethral resection syndrome, urinary retention, and permanent incontinence. Conclusion: Transurethral electrical vaporization of the prostate (TUVP) is a good, safe, effective and less costly method to transurethral resection of the prostate(TURP).